Comparing marginal microleakage in Class V cavities restored with flowable composite and Cention-N using confocal microscope-an in-vitro study - Pratima R Shenoi; Vandana B Kokane; Himani V Thawale; Rajesh R Kubde; Mohit K Gunwal; Shriya P Shahu (Wolters Kluwer Medknow Publications, 2021)
Context: Class V cavity presents a clinical challenge in the field of restorative dentistry as the margin placement is partially in enamel and partly in cementum, and the trouble associated with this design is the microleakage at the tooth restoration interface. Aims: To evaluate and compare marginal microleakage in Class V cavities when restored with flowable composite and Cention-N restorative material. Methods and Material: This in-vitro study was performed on 30 human maxillary premolars, which were extracted for orthodontic reasons. Class V cavities were prepared on the buccal surfaces of each tooth. After application of seventh-generation bonding agent (3M ESPE, Single Bond Universal Adhesive), the teeth were divided into two groups of 15 each and restored with flowable composite (3M ESPE Filtek Z350 XT) and Cention-N (Ivoclar Vivadent) and were subjected to thermocycling. The teeth were then immersed in 0.1% Rhodamine B dye for 48 h. They were sectioned longitudinally into mesial and distal parts with the help of an isomet diamond saw. The sections were observed under a confocal laser scanning microscope (CLSM). Statistical Analysis Used: The results were subjected to statistical analysis using the Mann-Whitney U test and Pearson's Chi-square test. Results: The analysis showed statistically significant results among the groups. Cention-N showed lesser microleakage, which was statistically significant when compared to flowable composite (P = 0.005). Conclusions: Cention-N showed significantly lesser leakage and better adaptation than flowable composite.